Impact of human papillomavirus on the tumor microenvironment in oropharyngeal squamous cell carcinoma. Issue 3 (3rd November 2021) - Liu, Xinyi; Liu, Ping; Chernock, Rebecca D.; Lang Kuhs, Krystle A.; Lewis, James S.; Li, Hua; Gay, Hiram A.; Thorstad, Wade L.; Wang, Xiaowei
Abstract: Increasing evidence has elucidated the clinicopathological significance of tumor microenvironment (TME) cells. However, TME differences associated with human papillomavirus (HPV) infection in oropharyngeal squamous cell carcinoma (OPSCC) have not been well characterized. In our study, we comprehensively determined the TME infiltration patterns in 315 OPSCC patients, and systematically correlated the TME phenotypes with genomic characteristics and clinical features of OPSCCs. In this way, we observed the enrichment of high endothelial cells and adaptive immune cells in HPV‐positive (HPV+) OPSCCs, in contrast to the enrichment of fibroblasts and capillary endothelial cells in HPV− negative (HPV−) OPSCCs. By focusing on immune checkpoint genes, we constructed a coexpression network using genes that were differentially expressed between HPV+ and HPV− OPSCCs. Functional analysis of the network indicated that HPV+ OPSCCs had elevated immune activities by promoting adaptive immune response and suppressing activities related to extracellular matrix organization. Subsequently, clinical analysis showed that identified TME‐relevant genes were closely associated with the prognosis and therapy response in OPSCC. Importantly, results from the TME analysis were further validated using an independent OPSCC cohort. Abstract : What's new? The tumor microenvironment has become increasingly important in understanding the molecular and clinical behavior of malignant tumors. Might the presence of an oncogenic virus further change the tumor microenvironment? In this study, the authors used RNA‐seq profiling to identify cell types and immune‐checkpoint gene expression that differed between HPV‐positive vs. HPV‐negative oropharyngeal squamous cell carcinomas (OPSCC). These results may provide new therapeutic targets for OPSCC treatment.